Investigation of activin A in inflammatory responses of the testis and its role in the development of testicular fibrosis. Issue 8 (24th July 2019) - Kauerhof, A Christine; Nicolas, Nour; Bhushan, Sudhanshu; Wahle, Eva; Loveland, Kate A; Fietz, Daniela; Bergmann, Martin; Groome, Nigel P; Kliesch, Sabine; Schuppe, Hans-Christian; Pilatz, Adrian; Meinhardt, Andreas; et al.
Abstract: STUDY QUESTION: Does activin A contribute to testicular fibrosis under inflammatory conditions? SUMMARY ANSWER: Our results show that activin A and key fibrotic proteins are increased in human testicular biopsies with leukocytic infiltrates and impaired spermatogenesis and in murine experimental autoimmune orchitis (EAO) and that activin A stimulates fibrotic responses in peritubular cells (PTCs) and NIH 3T3 fibroblasts. WHAT IS KNOWN ALREADY: Fibrosis is a feature of EAO. Activin A, a regulator of fibrosis, was increased in testes of mice with EAO and its expression correlated with severity of the disease. STUDY DESIGN, SIZE, DURATION: This is a cross-sectional and longitudinal study of adult mice immunized with testicular homogenate (TH) in adjuvant to induce EAO, collected at 30 ( n = 6), 50 ( n = 6) and 80 ( n = 5) days after first immunization. Age-matched mice injected with adjuvant alone ( n = 14) and untreated mice ( n = 15) were included as controls. TH-immunized mice with elevated endogenous follistatin, injected with a non-replicative recombinant adeno-associated viral vector carrying a gene cassette of follistatin (rAAV-FST315; n = 3) or vector with an empty cassette (empty vector controls; n = 2) 30 days prior to the first immunization, as well as appropriate adjuvant ( n = 2) and untreated (n = 2) controls, were also examined. Human testicular biopsies showing focal inflammatory lesions associated with impaired spermatogenesis ( n = 7) were included. Biopsies showing intact spermatogenesis without inflammation, from obstructive azoospermia patients, served as controls ( n = 7). Mouse primary PTC and NIH 3T3 fibroblasts were stimulated with activin A and follistatin 288 (FST288) to investigate the effect of activin A on the expression of fibrotic markers. Production of activin A by mouse primary Sertoli cells (SCs) was also investigated. PARTICIPANTS/MATERIALS, SETTING, METHODS: Testicular RNA and protein extracts collected from mice at days 30, 50 and 80 after first immunization were used for analysis of fibrotic marker genes and proteins, respectively. Total collagen was assessed by hydroxyproline assay and fibronectin; collagen I, III and IV, α-smooth muscle actin (α-SMA) expression and phosphorylation of suppressor of mothers against decapentaplegic (SMAD) family member 2 were measured by western blot. Immunofluorescence was used to detect fibronectin. Fibronectin ( Fn ), αSMA ( Acta2 ), collagen I ( Col1a2 ), III ( Col3a1 ) and IV ( Col4a1 ) mRNA in PTC and NIH 3T3 cells treated with activin A and/or FST288 were measured by quantitative RT-PCR (qRT-PCR). Activin A in SC following tumour necrosis factor (TNF) or FST288 stimulation was measured by ELISA. Human testicular biopsies were analysed by qRT-PCR for PTPRC ( CD45) and activin A ( INHBA), hydroxyproline assay and immunofluorescence. MAIN RESULTS AND THE ROLE OF CHANCE: Production of activin A by SC was stimulated by 25 and 50 ng/ml TNF ( P < 0.01, P < 0.001, respectively) as compared to untreated cells. INHBA mRNA was increased in human testicular biopsies with leukocytic infiltrates and impaired spermatogenesis, compared with control biopsies ( P < 0.05), accompanied by increased total collagen ( P < 0.01) and fibronectin deposition. Total testicular collagen ( P < 0.0001) and fibronectin protein expression ( P < 0.05) were also increased in EAO, and fibronectin expression was correlated with the severity of the disease ( r = 0.9028). In animals pre-treated with rAAV-FST315 prior to immunization with TH, protein expression of fibronectin was comparable to control. Stimulation of PTC and NIH 3T3 cells with activin A increased fibronectin mRNA ( P < 0.05) and the production of collagen I ( P < 0.001; P < 0.01) and fibronectin ( P < 0.05). Moreover, activin A also increased collagen IV mRNA ( P < 0.05) in PTC, while αSMA mRNA ( P < 0.01) and protein ( P < 0.0001) were significantly increased by activin A in NIH 3T3 cells. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: A limited number of human testicular specimens was available for the study. Part of the study was performed in vitro, including NIH 3T3 cells as a surrogate for testicular fibroblasts. WIDER IMPLICATIONS OF THE FINDINGS: Resident fibroblasts and PTC may contribute to the progression of testicular fibrosis following inflammation, and activin A is implicated as a key mediator of this process. STUDY FUNDING/COMPETING INTEREST(S): This work was supported by the National Health and Medical Research Council of Australia, the Victorian Government's Operational Infrastructure Support Program and the International Research Training Group between Justus Liebig University (Giessen) and Monash University (Melbourne) (GRK 1871/1–2) on `Molecular pathogenesis on male reproductive disorders' funded by the Deutsche Forschungsgemeinschaft and Monash University. The authors declare no competing financial interests.